A new and simple model for the prediction of horizontal well productivity in gas condensate reservoirs. (1st July 2018) - Ghahri, Panteha; Jamiolahmadi, Mahmoud; Alatefi, Ebrahim; Wilkinson, David; Sedighi Dehkordi, Farzaneh; Hamidi, Hossein
Highlights: Several in-house simulators used to simulate the horizontal well productivity. A new approach has been developed for estimation the productivity. Developed method has been tested and confirmed against synthetic data. Abstract: Horizontal well drilling is a well-established technology to enhance well productivity by increasing reservoir contact compared to that of vertical wells under the same conditions. In gas condensate reservoirs, in addition to the three-dimensional (3D) nature of the flow geometry around the horizontal well, the flow behaviour is further complicated by the phase change and the variation of relative permeability (kr ) due to the coupling (increase in kr by an increase in velocity or decrease in IFT) and inertia (a decrease in kr by an increase in velocity) effects. There are no practically attractive simple methods for well productivity calculations that account for these effects. Therefore, as an alternative, numerical simulation of such a complex 3D flow using commercial numerical simulators is usually adopted. This approach requires a 3D fine grid compositional approach which is very demanding, cumbersome and often associated with convergence problems due to numerical instability. Consequently, the introduction of a quick and reliable tool for long term well productivity calculations for gas-condensate systems is the main objective of the present work. An in-house simulator was developed to realistically simulate the multiphase flow of gas and condensate around horizontal wells. Using this model, a large data bank was then generated covering the impact of a wide range of pertinent geometric and flow parameters on well performance including: well and reservoir geometries, reservoir and bottom-hole pressure, fluid velocity, gas oil ratio and fluid composition. Based on the results of these simulations, a new method has been proposed to predict the productivity of horizontal wells for gas and condensate systems. In this approach, the flow behaviour of gas and condensate around the well is quantified in terms of the effective wellbore radius of an equivalent open hole that replicates flow around the actual 3D system. The effective wellbore radius varies with fluid properties, velocity and interfacial tension (IFT), reservoir and wellbore conditions. The integrity of the new methodology has also been verified for various fluids and flow conditions. This approach, included in a simple spreadsheet, can predict the horizontal well performance, significantly facilitating engineering and management decisions on the application of costly horizontal well technology.